(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Denaturation of proteins plays a crucial part in cellular activities. In this study, we have investigated the folding unfolding pathways of zebrafish dihydrofolate reductase (zDHFR) in presence of different chemical denaturants which were found to be an influential factor for the refolding yield by UV-visible spectrophotometric analysis. The activity change of zDHFR has been observed in presence of three different denaturants like Acetic Acid (AcOH), Sodium Dodecyl Sulphate (SDS), and Ethanol (C2H5OH). Spectrophotometric analysis reveals that protein unfolded completely at different concentrations and times by these denaturants. The spontaneous refolding experiments of chemically denatured zDHFR were also conducted to verify the spontaneous refolding yield. These investigations have helped us to decipher a picture about the denaturants contributing to achieving the refolding yield. We observed that acetic acid is a stronger denaturant among all, and the spontaneous refolding yields were higher from SDS denaturation. In the light of the above findings, higher spontaneous refolding yields were obtained from the low concentration of denaturants.